School sports in the Balkan countries: A comparative study - Marković Srđan R.; Grbović Marija N.; Bogavac Dragana S. (Zbornik radova (Univerzitet u Kragujevcu. Pedagoški fakultet u Užicu))
School sports are part of both the educational and sports systems, and they are regulated differently in some countries. Accordingly, the aim of this paper is to make a comparative analysis of the management models of school sports in 5 Balkan countries: Serbia, Croatia, Slovenia, Bosnia and Herzegovina, and Montenegro. The systems were observed based on four criteria: documents forming the basis of the school sport model, financing, the system of school sport competitions, and the branching of the system. It was established that in all models from the observed countries there are general and specific documents that are important for the functioning of school sports. Although the management structure is similar in all observed models, the control by individual sectors is carried out seriously only in Slovenia. In all models, only physical education teachers are responsible for the implementation of all programs and projects. Also, insufficient and unsystematic financing of school sports can be observed in all countries (except Slovenia), which results in problems in the implementation of school sports competitions. Based on the characteristics of the examined models of school sports, it was determined that the organization and management of school sports in Slovenia contributed to better results in terms of criteria that can be used to assess the quality of school sports.